Success of dental implants in smokers and non-smokers: a systematic review and meta-analysis. Issue 2 (February 2016) - Moraschini, V.; Barboza, E. dS. Porto
Abstract: The purpose of this review was to test the null hypothesis of no difference in marginal bone loss and implant failure rates between smokers and non-smokers with respect to the follow-up period. An extensive electronic search was performed in PubMed, Web of Science, and the Cochrane Central Register of Controlled Trials to identify relevant articles published up to February 2015. The eligibility criteria included randomized and non-randomized clinical studies. After an exhaustive selection process, 15 articles were included. The meta-analysis was expressed in terms of the odds ratio (OR) or standardized mean difference (SMD) with a confidence interval (CI) of 95%. There was a statistically significant difference in marginal bone loss favouring the non-smoking group (SMD 0.49, 95% CI 0.07–0.90; P = 0.02). An independent analysis revealed an increase in marginal bone loss in the maxilla of smokers, compared to the mandible (SMD 0.40, 95% CI 0.24–0.55; P < 0.00001). A statistically significant difference in implant failure in favour of the non-smoking group was also observed (OR 1.96, 95% CI 1.68–2.30; P < 0.00001). However, the subgroup analysis for follow-up time revealed no significant increase in implant failure proportional to the increase in follow-up time ( P = 0.26).